Efektivitas Tumbuhan Sungkai (Albertisia papuana Becc) Suku Dayak Ngaju Dalam Mempengaruhi Hasil Hematologi Hewan Coba Diabetes Mellitus Tikus Putih (Rattus norvegicus) - Dery Ade Pramana (Jurnal Kesehatan Indonesia, 2026)
Diabetes is a type of degenerative disease in which blood glucose levels are not properly regulated by the body. The progression of this disease can be minimized through the presence of antioxidants in the body. Sungkai (Peronema canescens) is a plant known to have high antioxidant activity, making it a potential alternative for the treatment of diabetes mellitus. This plant has been traditionally used by the Dayak Ngaju tribe to manage diabetes mellitus. The purpose of this study is to determine whether the antioxidant content in sungkai can improve the quality of hematological parameters in white rats (Rattus norvegicus) used as an experimental model for diabetes mellitus. The data obtained will be statistically analyzed using ANOVA, followed by tests of normality, homogeneity, and a post hoc Duncan test. The results indicate that the antioxidant content in sungkai has the potential to improve the hematological status of diabetic rats.